The Problem of Own and Alien in Dovlatov’s Cycle “Suitcase” - Mahbobzadh, Sara; Harisovna Nasrutdinova, Liliya; Munjal, Girish (International Journal of Criminology and Sociology, 2022)
The article deals with various aspects of the reception of the concepts "Own" and "Alien" in S. Dovlatov’s "Suitcase" cycle: material, ideological, philosophical, socio - and ethnocultural, etc. Special attention is paid to the reception of the categories of Soviet and official as not-Own. An important component of the problem of Own and Alien in the "Suitcase" cycle is also the attitude of the hero-narrator to Soviet and American culture. Widely articulated desire to associate his biography and professional activities allows us to conclude about the hero’s attempt to position himself as a person outside the Soviet system. The appeal to the realities of culture helps the author to identify their value orientations and express their attitude to people and the world. Certainly, the significance of the problem of the correlation of Own and Alien in the literary heritage of S. Dovlatov is predetermined by his status as a dissident writer and an immigrant writer. However, the writer is not characterized by a tendency toward the antithetic character of creating an opposition between Own and Alien. In the art world of S. Dovlatov, there are no types of "stigmatized Alien" and "hostile Alien". Moreover, the model of his interaction with the world is defined as "Own among your Own".